PERSEPSI KUALITAS IMPLEMENTASI CUSTOMER RELATIONSHIP MARKETING, PENGARUHNYA TERHADAP NILAI PELANGGAN, KEUNGGULAN PRODUK DAN KEPUASAN PELANGGAN (Studi pada Fakultas Ekonomi dan Bisnis UNSOED) - Sumarsono Sumarsono; Yayat Giyatno; Retno Widuri (JBIMA (Jurnal Bisnis dan Manajemen), 2014)
This study attempts to identify the perceptions of students of Economics and Business Faculty of the CRM implementation and its influence on the formation of customer value, product excellence and customer satisfaction. The concept of customer in this study was focused on the student. While the implementation of CRM in this study was focused on the Academic Information System (SIA).The purpose of the study was 1) to analyze the students' perceptions of the implementation of Customer Relationship Marketing (CRM) at the Faculty of Economics and Business UNSOED, 2) to analyze the effect of the implementation of CRM on Customer Value and Product Advantage, and 3) to analyze the effect of Customer Value and Product Advantage to Customer Satisfaction.The sample of the study was 116 students of the Faculty of Economics and Business, qualitative descriptive analysis and Structural Equation Modeling (SEM) was used to analyze the data collected. The result show that students' perceptions of the implementation of Customer Relationship Marketing (CRM) at the Faculty of Economics and Business UNSOED was positive, 2) Implementation of CRM has a positive effect on Customer Value and Product Advantage, and 3) Customer Value and Product Advantage has a positive effect on Customer Satisfaction. The results of this study are expected to be input for Jenderal Soedirman University to improve their service quality.